Dampak Media Sosial Bagi Mahasiswa TBI - Eka Susanti; Aisyah Hafizha; Amanda Amanda; Nursyahrina Lubis (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2024)
The role of social media for students, namely to improve the quality of student education, has become an important focus in the development of the contemporary education system. The presence of social media has brought significant changes in the way students and educators interact, collaborate and learn. This paper investigates the impact of social media in education, considering its positive and negative aspects. On the positive side, social media provides easy access to information, enables collaboration and project-based learning, and facilitates the development of digital and professional skills. Students are recorded as having used social media before entering college. They at least have more than one social media account. This research aims to investigate the role of social media in improving the quality of student education by analyzing how the impact of social media such as social structure, culture and interactions between individuals influence the learning process. The research method used involved literature analysis and case studies to understand the impact of social structure, culture, and social interactions on the educational experiences of TBI students. By understanding the social dynamics in the classroom, educators can adopt more effective strategies to overcome the challenges faced by students in learning. Through this approach, social media has an impact as an important tool in shaping educational policies that are more inclusive and responsive to the needs of diverse students. By examining the various impacts of social media on educational opportunities, social media can encourage the adoption of policies that are inclusive and responsive to the needs of diverse students.